Composite hyaluronate-type I collagen-fibrin scaffold in the therapy of osteochondral defects in miniature pigs - Filová, Elena; Rampichová, Michala; Handl, Milan; Lytvinets, Andriy; Halouzka, Roman; Usvald, Dušan; Juhásová, Jana; Procházka, Radek; Dezortová, Monika; Rolencová, Eva; Kuželová Košťáková, Eva; Trč, Tomáš; et al. (Physiological research, 2007)
The potential of novel scaffold containing sodium hyaluronate, type I collagen, and fibrin was investigated in the regeneration of osteochondral defects in miniature pigs. Both autologous chondrocyte-seeded scaffolds and non-seeded scaffolds were implanted into two defects located in the non-weight-bearing zone of the femoral trochlea (defect A was located more distally and medially, defect B was located more proximally and laterally). Control defects were left untreated. Twelve weeks after the operation, the knees were evaluated in vivo using MRI. Six months after the implantation, the defects were analyzed using MRI, histological, and immunohistochemical analysis. In the A defects of chondrocyte-seeded scaffold group, hyaline cartilage and fibrocartilage was formed, containing type II collagen, acidic and neutral glycosaminoglycans while the non-seeded scaffold group was predominantly filled with fibrocartilage. Defects in the control group were predominantly filled with fibrous tissue. Histomorphometric analysis of photomicrographs revealed a significantly higher amount of hyaline cartilage in the cell-seeded scaffold group in A defects than in other groups. Both scaffold groups in A defects showed significantly less fibrous tissue than cell-seeded defects B and the control group. Both histological and MRI analysis proved that the novel composite scaffold has a potential to regenerate osteochondral defects within six months.
Keywords: nemoci chrupavky; hyalinní chrupavka; Animals; Swine, Miniature; kolagen typu I; Magnetic Resonance Imaging; tkáňové podpůrné struktury; chondrocyty; Glycosaminoglycans; biokompatibilní materiály; glykosaminoglykany; Time Factors; časové faktory; Collagen Type II; Fibrin; Immunohistochemistry; tkáňové inženýrství; miniaturní prasata; magnetická rezonanční tomografie; prasata; Chondrocytes; kyselina hyaluronová; kultivované buňky; imunohistochemie; Hyaluronic Acid; Hyaline Cartilage; Biocompatible Materials; Cells, Cultured; Fibrocartilage; modely nemocí na zvířatech; Swine; vazivová chrupavka; fibrin; Cartilage Diseases; Disease Models, Animal; Stifle; kolagen typ II; Tissue Engineering; zvířata; Collagen Type I; Tissue Scaffolds; kolenní kloub u koně, psa